KEPENTINGAN INDONESIA BEKERJA SAMA DENGAN INDIA DALAM IMPOR GULA MENTAH - Handayani, Anita Sri; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Until now, Indonesia is still always faced with the problem of sugar production which has not been able to meet domestic needs. This inability can be seen from the lower production of sugarcane plantations by farmers and the need to revitalize old factories.The method used in this research is descriptive analytical method. The perspective used is the perspective of liberalism, the perspective of liberalism says that humans basically have good behavior and humans have the power to share with each other by cooperating. The theory used in this is the theory of interdependence, the theory of interdependence is the interdependence of each other or can be called reciprocal relations in international relations.The high level of Indonesian sugar consumption is inversely proportional to the unbalanced amount of production. This imbalance is trying to be covered by importing sugar, both raw sugar (Raw Sugar), white crystal sugar and refined sugar. India became one of the countries that Indonesia went to to import raw sugar even though at first India was not a country that imported sugar into Indonesia. Based on the results of the discussion analysis, it can be concluded that Indonesia imports raw sugar from India to meet domestic needs and also to achieve Indonesia's economic and political interests.  Keywords: production, imports, raw sugar, interdependence theory liberalism  perspective